Undernutrition fetal programming: effects on kidney morphology, renal steroid and angiotensin receptors expression and urinary sodium excretion - Cardoso, Bárbara Vaccari [UNESP] (2011)
Maternal undernutrition affects the foetal development, promoting renal alterations and adult hypertension. The present study investigates, in adult male rats, the effect of food restriction in utero on arterial blood pressure changes (AP), and its possible association with the number of nephrons, renal function and angiotensin II (AT1R/AT2R), glucocorticoid (GR) and mineralocorticoid (MCR) receptors expression. The daily food supply to pregnant rats was measured and one group (n=5) received normal quantity of food (NF) while the other group received 50% of that (FR50) (n=5). The AP was measured weekly. At 16 weeks of life, fractionator’s method was used to estimate glomeruli number in histological slices. The renal function was estimate by creatinine and lithium clearances. Blood and urine samples were collected to biochemical determination of creatinine, sodium, potassium and lithium. At 90th and 23rd days of life, kidneys were also processed to AT1R, AT2R, GR and MCR immunolocalization and for western blotting analysis. FR50 offspring shows a significant reduction in BW (FR50: 5.67 ± 0.16 vs. 6.84 ± 0.13g in NF, P<0.001) and increased AP from 6th to 12nd week (6thwk FR50: 149.1 ± 3.4 vs. 125.1 ± 3.2mmHg in NF, P<0.001and, 12ndwk FR50: 164.4 ± 4.9 vs. 144.0 ± 3.3 mmHg in NF, P=0.02). Expression of AT1R and AT2R were significantly decreased in FR50 (AT1, 59080 ± 2709 vs. 77000 ± 3591 in NF, P=0.05; AT2, 27500 ± 95.50 vs. 67870 ± 1509 in NF, P=0.001) while the expression of GR increased in FR50 (36090 ± 781.5 vs. 4446 ± 364.5 in NF, P=0.0007). The expression of MCR did not change significantly. We also verified a pronounced decrease in fractional urinary sodium excretion in FR50 offspring (0.03 ± 0.02 vs. 0.06 ± 0.04 in NF, p=0.03). This occurred despite unchanged creatinine clearance. The study led us to suggest that fetal undernutrition, with increased fetal exposure... (Complete abstract click electronic access below)